The Current Treatment Paradigm for Pancreatic Ductal Adenocarcinoma and Barriers to Therapeutic Efficacy - Principe, Daniel R.; Underwood, Patrick W.; Korc, Murray; Trevino, Jose G.; Munshi, Hidayatullah G.; Rana, Ajay (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) has a dismal prognosis, with a median survival time of 10-12 months. Clinically, these poor outcomes are attributed to several factors, including late stage at the time of diagnosis impeding resectability, as well as multi-drug resistance. Despite the high prevalence of drug-resistant phenotypes, nearly all patients are offered chemotherapy leading to modest improvements in postoperative survival. However, chemotherapy is all too often associated with toxicity, and many patients elect for palliative care. In cases of inoperable disease, cytotoxic therapies are less efficacious but still carry the same risk of serious adverse effects, and clinical outcomes remain particularly poor. Here we discuss the current state of pancreatic cancer therapy, both surgical and medical, and emerging factors limiting the efficacy of both. Combined, this review highlights an unmet clinical need to improve our understanding of the mechanisms underlying the poor therapeutic responses seen in patients with PDAC, in hopes of increasing drug efficacy, extending patient survival, and improving quality of life.